BISNIS MILITER PASCA ORDE BARU - NUR KHAIRUNISA SUGIARTO (CosmoGov: Jurnal Ilmu Pemerintahan, 2018)
After the fall of the Suharto regime, the TNI's existence as a socio-political force was sued by many parties. They assume that TNI should not occupy positions outside of Hankam that should be a portion of civilian groups. According to Bilveer Singh, in most western societies, the role of the military is essentially to support the political aspirations of society under civilian leadership. This statement is based on the opinion of Samuel P. Hutington who said that the majority of military professionals in the west accept civil power as a right that should exist. Therefore, when the military "deviates" and interferes in civil affairs, then, as Taufik Abdullah says, there is a concern based on the assumption that illegal acts have been committed. Thoughts that place the military as a civic-supporting force to carry out the affairs of its "part" are not fully applied in third world countries including Indonesia. Studies showing military intervention in politics show that military interests and the crisis facing a country push the military to interfere in civil affairs. Military intervention in politics can not be separated from military control in other fields such as economics.